The Difficulty with Diversity: White and Aboriginal Women Workers’ Representations of Diversity Management in Forest Processing Mills - Mills, Suzanne (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2011)
Abstract This paper critically examines diversity management in a multinational forest company in Saskatchewan, Canada. Drawing on insights from intersectionality theory, it highlights how white and Aboriginal women’s experiences inform our understanding of workplace practices to include marginalized groups. Scholars in organization studies have critiqued diversity management for how its underlying individualism translates into a narrow understanding of difference. This critique is complicated by demonstrating how women’s experiences and representations of diversity management were uneven. Women’s portrayals of diversity management were structured by their gender, class, and by whether they were white or Aboriginal. Women’s experiences and representations extend critiques of diversity management by uncovering some of the ways that corporate liberal ideology works through local constructions of difference. Since diversity management did not challenge white women’s beliefs of meritocracy, it helped to re-inscribe racism towards Aboriginal peoples.